The Narrative Structure of Ashab al-Kahf Story - Amrulloh, Muhammad Afif; Qalyubi, Syihabuddin; Dewi, Eva; Zahra, Dwi Noviatul; Kurniawan, Rahadian (Institut Agama Islam Negeri Curup, 2022)
This paper examined the narrative structure, language style, and chronology of AÅŸá¸¥Äb Al-Kahfi story in Al-Qur'an. The research data were obtained from Al-Qur'Än. The Qurâ€™anic verses which told about AÅŸá¸¥Äb Al-Kahf were collected in Surah Al-Kahf (18) verses 9-26. The results showed that the narrative structure of this story consists of orientation I, sequence of events I, coda I, complication, orientation II, sequence of events II, orientation III, coda II, orientation IV, and resolution. These structures are interrelated and form a logical, holistic, and beautiful story unit that fulfil all elements of Mark Andersonâ€™s and Kathryn Andersonâ€™s narrative-structure concepts. Meanwhile, the dialogue style dominates in the presentation of stories that are in accordance with the journey of the Prophetâ€™s daâ€™wa. The dialogue style used in the presentation of the story is calm and acceptable. This style is intended to defend the call of the prophet's da'wa and refute peopleâ€™s rejection in the middle Meccan period through the theme of monotheism value and the mention of Allahâ€™s powers. This study contributes to putting the theory of stylistics and narratology in the reading of story verses. Hence, this paper suggests a further study of the story verse covering the narrative structureâ€™s meaning and function as well as aspects of the beauty of pronunciation and story verse meanings.